The study of directional overcurrent relay and directional earth-fault protection application for 33 kV underground cable system in Malaysia - Bakar, A.H.A.; Mokhlis, Hazlie; Illias, N.A.; Chong, P.L. (International Journal of Electrical Power & Energy Systems, 2012)
Differential protection scheme is based on comparison of measured variables such as current and voltage at the two ends of a line via a communication channel such as pilot wire. This scheme is preferred and extensively used in distribution feeder protection system in Malaysia due to its fast operation. However pilot-wire differential scheme has its own drawbacks especially on the maintenance of the pilot-wire. Once the plot-wire is out of service, the feeder protection is jeopardised. One of the options to overcome such maintenance issue is to adopt directional relay as I he feeder protection. This paper investigates a suitable relay connection and the maximum torque angle for the directional relay for 33 kV underground network. In this study, a section of 33 kV underground network in Kuala Lumpur (KL) city has been analysed. All faults types have been simulated at all possible location in the network. The obtained voltage and current were then used to determine the operation of directional overcurrent and earth-fault relay. The simulation results indicate that 30 degrees relay connection with 0 degrees maximum torque angle (30 degrees/0 degrees) is the most suitable setting to be applied for 33 kV underground network in KL, as against the best general and most versatile setting, 45 degrees/90 degrees.